2019
DOI: 10.3390/molecules24244493
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic SNF-Approach to Fluorinated Phenyl tert-Butyl Nitroxides

Abstract: The interaction of octafluorotoluene (1a), as well as pentafluorobenzonitrile (1b) with tert-butylamine, followed by the oxidation of thus formed tert-butylanilines (2a,b) with meta-chloroperoxybenzoic acid led to functionalized perfluorinated phenyl tert-butyl nitroxides [namely, 4-(N-tert-butyl(oxyl)amino)heptafluorotoluene (3a) and 4-(N-tert-butyl(oxyl)amino)tetrafluorobenzonitrile (3b)] with nearly quantitative total yields. The molecular and crystal structures of nitroxide 3a were proved by single crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 50 publications
3
11
0
Order By: Relevance
“…It was revealed that radical 4 crystallizes in the orthorhombic Pbca space group ( Table 1 ). Bond lengths of the tert -butylnitroxide moiety ( Table 2 ) are fully consistent with those of previously described radicals of this family [ 3 ]. The nitroxide groups in diradical 4 are twisted at a large angle (~64°) relative to the aromatic ring.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…It was revealed that radical 4 crystallizes in the orthorhombic Pbca space group ( Table 1 ). Bond lengths of the tert -butylnitroxide moiety ( Table 2 ) are fully consistent with those of previously described radicals of this family [ 3 ]. The nitroxide groups in diradical 4 are twisted at a large angle (~64°) relative to the aromatic ring.…”
Section: Resultssupporting
confidence: 88%
“…Recently, we proposed a new synthetic approach to obtaining functionalized tert -butylphenylnitroxides by sequential substitution of a fluorine atom in polyfluorinated arenes with tert -butylamine or lithium tert -butylamide and oxidation of resultant N - tert -butylanilines with meta -chloroperoxybenzoic acid ( m -CPBA). This approach has been found to generate nitroxide mono- and diradicals in high yields ( Figure 1 ) [ 3 , 4 ]. Moreover, it turned out that polyfluorinated tert -butylarylnitroxides are much stable than nonfluorinated analogs.…”
Section: Introductionmentioning
confidence: 99%
“…Diradical 3 crystallizes in the monoclinic P2 1 /c space group. Bond lengths of the tert-butylnitroxide moiety are completely compatible with those of previously described radicals of this family [25]. The nitroxide groups in diradical 3 are twisted by different and large angles (~65 • and~70 • ) relative to the aromatic rings, as are the aromatic rings toward each other (~53 • , Figure 3a).…”
Section: Electrochemical Properties Of Nn′-(perfluorobiphenyl-44′-dsupporting
confidence: 87%
“…Diradical 3 featured an irreversible oxidation wave with E 1/2 ≈ 0.98 V, which was assigned to the oxidation of the nitroxide radicals into the corresponding oxoammonium cations. On the cathodic side, nitroxide diradical 3 also showed irreversible redox at −1.43 V. The redox potentials of diradical 3 are very close to those of fluorinated phenyl-tert-butylnitroxides reported by us previously [25].…”
Section: Electrochemical Properties Of Nn′-(perfluorobiphenyl-44′-dsupporting
confidence: 84%
See 1 more Smart Citation